2010
DOI: 10.1055/s-0030-1262826
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Maternal Hypothyroidism on the Carbohydrate Metabolism and Insulin Secretion of Isolated Islets in Adult Male Offspring of Rats

Abstract: Thyroid hormones have crucial developmental effect during fetal life. This study investigates the effects of maternal hypothyroidism on the carbohydrate metabolism and insulin secretion capacity of islets of the adult male offspring of rats. One group of pregnant mothers (fetal hypothyroid) of Wistar rats drank water containing 0.02% of 6-propyl-2-thiouracil during pregnancy, while the control group consumed only tap water. After delivery, survival and weight of the neonates from both groups were followed. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 32 publications
8
23
0
Order By: Relevance
“…In our study, TCH rats had lower weight both at birth and until month 3, similar to previous reports [10, 11]. Weight gain was, however, similar between groups during months 3 to 19; a finding in keeping with our previous reports on TCH rats followed until month 12 [10, 44].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, TCH rats had lower weight both at birth and until month 3, similar to previous reports [10, 11]. Weight gain was, however, similar between groups during months 3 to 19; a finding in keeping with our previous reports on TCH rats followed until month 12 [10, 44].…”
Section: Discussionsupporting
confidence: 92%
“…The incidence of TCH is very low in iodine-sufficient areas such as the United States (1 in 50000) or very high in the iodine-deficient areas such as Europe (1 in 100) [6] and Africa (1 in 10) [9]. Hypothyroidism during pregnancy can cause glucose intolerance during adulthood [10, 11] that is a result of disturbed intrauterine conditions [12, 13]. …”
Section: Introductionmentioning
confidence: 99%
“…Fasting plasma glucose and insulin were measured to determine HOMA-IR index, the formula is: HOMA-IR=(c i ×c g )/22.5, where c i is fasting insulin level (µU/ml) and c g is fasting glucose level (mmol/L) (Farahani et al, 2010).…”
Section: Homeostasis Model Assessment Of Insulin Resistance (Homa-ir)mentioning
confidence: 99%
“…However, the important point is that the detrimental effect of TH deficiency begins in the early fetal life roughly after 12 weeks, which is the initiation of TH synthesis. Earlier studies revealed that fetal hypothyroidism has a worsening effect on brain development [22], cardiovascular development and functions [23,24], the reproductive system [25], skeletal muscle development [26] and glucose-insulin metabolism [27]. Additionally, optimizing the lipoprotein/lipid profile may take longer time.…”
Section: Discussionmentioning
confidence: 99%